Web-traffic filtering system - P. V. Pevnev (Литьë и металлургия)
The article provides an overview of the web traffic filtering system using the Linux-based Squid software package. The system allows you to limit users on the Internet and collect statistics without interfering with the user’s computer, including the web browser.